The Omega-3 Fatty Acids can Significantly Increase the Height of Children Under Five with Stunting - Lewi Jutomo1, Bambang Wirjatmadi2, Rudi Irawan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Children with stunting are a global public health problem that has implications for impaired physical growth, which has an impact on increasing morbidity and mortality. This study aims to study the role of omega-3 fatty acid supplementation on anthropometric measures of toddlers with stunting, especially height. This type of research was an experimental randomized clinical trial design, in the form of pre-post test control group design. Subjects who participated in this study were toddlers aged 12-36 months, consisting of 12 children as a control group who received placebo, and 12 children as a treatment group who received omega-3 fatty acid supplementation for 2 months. The parameters observed was height. The collected data were analyzed using t-test. The results of the study showed that there was a difference in changes in the subject’s height in the treatment group compared to the control group (p-value = 0.009294). It was further concluded that supplementation of omega-3 fatty acids in children under five with stunting could significantly increase height.